Promotion effectiveness of small scale enterprises (SMEs) in Indonesian unicorn marketplace - Ridha Rizki Novanda (Goodwood Publishing, 2023)
Purpose: These various activities certainly use no small cost in their operations. Therefore, it is necessary to re-analyze the customer's perception of the effectiveness of the SMEs promotion carried out by the unicorn startup marketplace in Indonesia. Research methodology: Data were gathered via survey software at purposefully selected research sites. Respondents, drawn accidentally from all Indonesian users of the Unicorn marketplace, completed closed questionnaires via a survey program using a Likert Scale. The study employed descriptive qualitative analysis and used EPIC rate analysis to evaluate the success of advertisements and impulse buying behavior. Results: Based on the EPIC rate score of 3.77, unicorn marketplace promotions have positively influenced customer perception. This average indicates that promotional activities significantly affect consumers' impulsive purchasing decisions. With sufficient influencing factors already in place, the marketplace aims to further enhance promotional efforts to boost impulse buying. Conclusion: Promotional strategies implemented by the unicorn marketplace have effectively influenced impulse buying behavior, revealing customer receptiveness and indicating strong potential for enhancing digital promotions in the future. Limitations: The study is limited to the SMEs sector and focuses solely on the promotional effectiveness of the Unicorn marketplace. Further research is needed to explore promotion through artificial intelligence. Contribution: This study offers insight into building digitally based SMEs, providing recommendations that support broader economic development initiatives.